Forty years of ocean acidification observations (1983–2023) in the Sargasso Sea at the Bermuda Atlantic Time-series Study site - Bates, Nicholas R.; Johnson, Rodney J. (Frontiers in Marine Science, 2023)
Ocean physical and biogeochemical conditions are rapidly changing over time. Forty years of observations from 1983 to 2023 collected at the Bermuda Atlantic Time-series Study (BATS) site near Bermuda in the North Atlantic Ocean shows continuing trends of surface warming, increase in salinity, loss of dissolved oxygen (DO), increase in carbon dioxide (CO2), and ocean acidification (OA) effects. Over this period, the ocean has warmed by about +1°C, increased in salinity by +0.136, and lost DO by 12.5 µmol kg−1 or 6%. Since the 1980s, ocean dissolved inorganic carbon (DIC), total alkalinity (TA), a tracer of anthropogenic CO2 (CTrOCA), and fugacities/partial pressures of CO2 (i.e., fCO2 and pCO2) have continued to increase substantially, with no evidence of a reduction in the rates of change over time. Contemporaneously, ocean pH has decreased by 0.1 pH units [with ocean acidity (i.e., H+) increasing by >30%], and the saturation states of calcium carbonate minerals (Ωcalcite and Ωaragonite) have decreased. These OA indicators show that the chemical conditions for calcification have become less favorable over the past 40 years. Updating of data and trends at the BATS site show how ocean chemistry of the 2020s is now outside the range observed in the 1980s, and how essential these data are for predicting the response of ocean chemistry and marine ecosystems to future shifting earth and ocean conditions.